If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(y + -3) = -6y + -12 + 2y Reorder the terms: -2(-3 + y) = -6y + -12 + 2y (-3 * -2 + y * -2) = -6y + -12 + 2y (6 + -2y) = -6y + -12 + 2y Reorder the terms: 6 + -2y = -12 + -6y + 2y Combine like terms: -6y + 2y = -4y 6 + -2y = -12 + -4y Solving 6 + -2y = -12 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. 6 + -2y + 4y = -12 + -4y + 4y Combine like terms: -2y + 4y = 2y 6 + 2y = -12 + -4y + 4y Combine like terms: -4y + 4y = 0 6 + 2y = -12 + 0 6 + 2y = -12 Add '-6' to each side of the equation. 6 + -6 + 2y = -12 + -6 Combine like terms: 6 + -6 = 0 0 + 2y = -12 + -6 2y = -12 + -6 Combine like terms: -12 + -6 = -18 2y = -18 Divide each side by '2'. y = -9 Simplifying y = -9
| 3a+12a=-7 | | 7.5a+9.2-6.8a-11b= | | -6(-1-3x)=-120 | | 9x^3+54x^2= | | 9x+3x=24 | | 4(2y-10)=3(2y+8) | | 3(5x+1)-2=3y+6 | | -2(y-3)=-6y-12+12y | | 4x-9y+3x= | | 3(y-10)+1=-5.5(y-8) | | X^2-5-35=0 | | -9(x-6)-4=50 | | -10x=-27x-17 | | x+3(1.25)=7.25 | | (4a-3b)(2a+6b)= | | 5xt-3xy= | | h(-0.5)=-4.5+3 | | y+.6=.8(y+2) | | y+.6=.8(y+2) | | Y=2b^2+4+9b | | [4x]=18+7y | | 2.3w+7+8.1+3w= | | 4.25*16= | | 10(2-m)-5(1-3m)=30 | | 0.53+0.34t=3.44t-0.71 | | 4y+16x=32 | | 0.53+0.34t=3.44t-0.71 | | 10(2-m)-5(1-3m)=30 | | 30+4n=95 | | 114=-6(2x-7) | | [7x-10]=X-6 | | 1.25+3y=7.25 |